Institutional pluralism and water user behavior in rural Africa. (April 2021) - Koehler, Johanna; Thomson, Patrick; Goodall, Susanna; Katuva, Jacob; Hope, Rob
Highlights: The study examines user commitment to professional service providers for rural water infrastructure emerging in Africa to advance the water SDG. Institutional pluralism is analyzed in terms of community, public, private and failed rural management arrangements applying cultural theory. Risks of different management cultures can be pooled under a pluralist arrangement in the form of a professional maintenance service. A novel methodological approach draws on panel data from 1215 households, sensor data from daily handpump usage and community responses. Contract commitment is associated with organizational, affordability and operational factors as well as environmental context. Abstract: The Sustainable Development Goal of providing everyone with safe and reliable drinking water services combines a moral imperative with an entrepreneurial opportunity. We examine water user behavior in the face of institutional change brought about by a professional service provider maintaining rural water infrastructure in Kenya. We ask (1) which factors are associated with households and waterpoint user groups contracting a service provider that guarantees rapid repairs; (2) how do factors vary between different management cultures defined by cultural theory of risk; and (3) can the professional service provider address the risk factors? By applying the cultural theory of risk framework, we capture the institutional diversity of community, public, private and failed management on the ground in dealing with operational, financial, institutional and environmental risks. To identify the factors associated with institutional change towards a pluralist arrangement – enabled by the professional maintenance service provider incubated in rural Kenya – we model data from 1215 households at actively managed handpumps with sensor data from daily handpump usage and community responses to this entrepreneurial approach. The predictors of behavior change of rural water users to commit to the new service provider include organizational factors of managing payments, affordability, and operational factors such as distance and water quality, which vary in importance across the management cultures. This learning can be harnessed to reduce risk and inform future policy and practice. As professional maintenance services for rural water infrastructure are emerging across Africa, which promise to increase value for rural water users, government, and investors through performance-based contracts, it is important for policymakers and implementers to understand which factors predict shifts in institutional behavior by water users. This research recommends seeking cooperative solutions across systems, where current policy effectively separates communities from the state or markets.